Influence of climate variability on seasonal and interannual variations of ecosystem CO2 exchange in flooded and non-flooded rice fields in the Philippines - Alberto, Ma. Carmelita R.; Hirano, Takashi; Miyata, Akira; Wassmann, Reiner; Kumar, Arvind; Padre, Agnes; Amante, Modesto (Field crops research, 2012)
► Flooded and aerobic fields can become weaker or stronger sinks of CO2 during ENSO. ► GPP of flooded field was more sensitive to increase in VPD than non-flooded field. ► The GPP in flooded rice was substantially larger than in aerobic rice. ► Flooded rice field had lower Re than non-flooded field when LAI was below 5 m2m−2. ► The Q10 values of flooded rice field was higher than non-flooded field. Seasonal rainfall in the Philippines is known to be modulated by ENSO phenomenon, with El Niño frequently contributing to reduced rainfall and drought while La Niña resulting in excessive rainfalls, floods and more intense typhoons. The alterations in rainfall patterns can have considerable feedback on solar radiation, air temperature, and soil moisture which can affect the ecosystem CO2 exchange. In this paper, we assessed the effects of the ENSO events (2008–mid 2010) on the seasonal climate conditions and determined how it affected the gross primary production (GPP), ecosystem respiration (Re), and net ecosystem production (NEP) of two contrasting rice environments: flooded and non-flooded. The 2008 dry season (DS) was under a La Niña event while the 2008 wet season (WS) was a neutral one with strong tropical cyclones associated during the wet season. The 2009DS was also La Niña while the 2009WS was El Niño; however, the northern part of the Philippines experienced strong tropical cyclones. The 2010DS was under an El Niño event. The La Niña in 2008DS resulted in about 15% lower solar radiation (SR), 0.3°C lower air temperature (Ta) and 60% higher precipitation compared to the 28-year climate normal patterns. Both flooded and non-flooded rice fields had lower NEP in 2008 DS (164 and 14gCm−2, respectively) than in 2008 WS (295 and 82gCm−2, respectively) because the climate anomaly resulted in SR – driven decrease in GPP. The La Niña in 2009DS even resulted in 0.2°C lower air temperature and 40% more precipitation than the 2008DS La Niña. This cooler temperature resulted in lower Re in flooded rice fields while the higher precipitation resulted in higher GPP in non-flooded fields since the climate was favorable for the growth of the aerobic rice, the ratoon crops and the weeds. This climate anomaly benefitted both flooded and non-flooded rice fields by increasing NEP (351 and 218gCm−2, respectively). However, NEP decreased in 2009WS in both flooded and non-flooded rice fields (225 and 39gCm−2, respectively) due to the devastating effects of the strong tropical cyclones that hit the northern part of the Philippines. On the other hand, the El Niño event during 2010DS resulted in about 6% higher solar radiation, 0.4°C higher air temperature and 67% lower precipitation than the 28-year climate normal pattern. The NEP of flooded and non-flooded rice fields were closely similar at 187 and 174gCm−2, respectively. This climate anomaly resulted in Ta – driven increase in Re, as well as vapor pressure deficit (VPD) – driven decrease in GPP in flooded rice fields. The GPP and Re in non-flooded rice fields were less sensitive to higher VPD and higher Ta, respectively. It appears that the net ecosystem CO2 exchange in non-flooded rice field was less sensitive to an El Niño event.